Root stem cell niche maintenance and apical meristem activity critically depend on THREONINE SYNTHASE1 - Reyes Hernández, Blanca Jazmín (The journal of experimental botany, 2019)
Indeterminate root growth depends on the stem cell niche (SCN) and root apical meristem (RAM) maintenance whose regulation permits plasticity in root system formation. Using a forward genetics approach, we isolated the moots koom1 (‘short root’ in Mayan) mutant that shows complete primary RAM exhaustion and abolished SCN activity. We identified that this phenotype is caused by a point mutation in the METHIONINE OVERACCUMULATOR2 (MTO2) gene that encodes THREONINE SYNTHASE1 and renamed the mutant as mto2-2. The amino acid profile showed drastic changes, most notorious of which was accumulation of methionine. In non-allelic mto1-1 (Arabidopsis thaliana cystathionine gamma-synthetase1) and mto3-1 (S-adenosylmethionine synthetase) mutants, both with an increased methionine level, the RAM size was similar to that of the wild type, suggesting that methionine overaccumulation itself did not cause RAM exhaustion in mto2 mutants. When mto2-2 RAM is not yet completely exhausted, exogenous threonine induced de novo SCN establishment and root growth recovery. The threonine-dependent RAM re-establishment in mto2-2 suggests that threonine is a limiting factor for RAM maintenance. In the root, MTO2 was predominantly expressed in the RAM. The essential role of threonine in mouse embryonic stem cells and in RAM maintenance suggests that common regulatory mechanisms may operate in plant and animal SCN maintenance.
Gesehen am 21.10.2019